2021
DOI: 10.1111/jnc.15544
|View full text |Cite
|
Sign up to set email alerts
|

Psychedelic‐inspired approaches for treating neurodegenerative disorders

Abstract: The atrophy of dendritic arbors, loss of dendritic spines, and reduction of synapse density in cortical regions controlling cognition, memory, and mood are hallmarks of Alzheimer's disease (AD), frontotemporal dementia (FTD), and related neurodegenerative dis-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 332 publications
(428 reference statements)
0
16
0
Order By: Relevance
“…Lucke-Wold B MedPress Publications LLC and tau hyperphosphorylation and accumulation [6]. Psychedelic medications are promising therapeutics in CTE for their ability to treat neuropsychiatric deficits and ability to promote neuroplasticity and suppress neuroinflammation and neurodegeneration [73][74][75][76][77][78][79][80][81][82][83][84].…”
Section: Medpress Psychiatry and Behavioral Sciencesmentioning
confidence: 99%
“…Lucke-Wold B MedPress Publications LLC and tau hyperphosphorylation and accumulation [6]. Psychedelic medications are promising therapeutics in CTE for their ability to treat neuropsychiatric deficits and ability to promote neuroplasticity and suppress neuroinflammation and neurodegeneration [73][74][75][76][77][78][79][80][81][82][83][84].…”
Section: Medpress Psychiatry and Behavioral Sciencesmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) is a key neuroplasticity-modulating neurotrophin that is involved in many physiological and pathological brain processes ( 221 , 222 ). It has been reported that psychedelics and related compounds, inducing the activation of AMPA and NMDA receptors, can positively modulate the levels of BDNF and/or neurotrophins which, inducing neuroplasticity, would ameliorate disorders originating from altered neuronal connectivity ( 223 ). For example, a single, low dose of LSD acutely increases BDNF levels in healthy volunteers ( 224 ).…”
Section: Psychedelicsmentioning
confidence: 99%
“…Most current psychedelic research is focused on the potential therapeutic effects of these compounds. In particular, studies suggest that psychedelics may be an effective treatment for a variety of clinical issues, including treatment-resistant depression (Carhart-Harris et al, 2021), cancer-related distress (Griffiths et al, 2016;Ross et al, 2016), obsessive compulsive disorder (Moreno et al, 2006), substance use disorders (Bogenschutz et al, 2015(Bogenschutz et al, , 2018Johnson, Garcia-Romeu, & Griffiths, 2017), eating disorders (Spriggs, Kettner, & Carhart-Harris, 2020), and neurodegenerative disorders (Saeger & Olson, 2021). Psychedelics have also been posited to promote healthy lifestyle changes (Lutkajtis, 2021;Madsen et al, 2020;Teixeira et al, 2022), increase nature-relatedness (Lyons & Carhart-Harris, 2018) and foster environmental virtues (Kirkham & Letheby, 2022).…”
Section: Introductionmentioning
confidence: 99%